Study the Effect of Plate and Nerve Type on the Behavior of Metal Joints in Fire Conditions - Mouhanad Faez Nasra (Tishreen University, 2020)
The study in this research will be on the metal joints used in metal structures by testing a number of different materials for the elements used to connect the beams with each other, with the help of the method of finishing elements 3D and CATIA V5 program. Column when exposed to virtual loads and simulators expose joints to fire. This article provides a detailed analysis of the effect of material type on the stresses produced by examining the effect of the change of material of the link elements (nerve and plate) on the values ​​of stress resulting to the degree of collapse. The elements were selected from several materials and mixtures consisting of different chemical elements where the stresses arising after the design and modeling of each link for each cell with a different nerve and plate were calculated by the presence of temperatures from the ambient temperature to the melting point of the studied mixtures. Type of material and chemical elements While all other parameters of the link (dimensions, shape, type of connection, fixation conditions, and ...) have been fixed to understand the effect of plate type and nerve on the stress values ​​arising in the link where there are many other factors that may affect stress values ​​such as more than P load and the occurrence of internal cracks in the metal resulting from operations etc .... الدراسة في هذا البحث ستكون على الوصلات المعدنية المستخدمة في المنشآت المعدنية وذلك عبر اختبار عدد من المواد المختلفة للعناصر المستخدمة في ربط العوارض مع بعضها البعض بمساعدة طريقة العناصر المنتهية ثلاثية الأبعاد و برنامج CATIA V5 .تم في هذا البحث دراسة سلوك وصلات من نوع جائز - عمود عند تعرضها لحمولات افتراضية ومحاكات تعرض الوصلات للحريق. تقدم هذه المقالة تحليلاً تفصيلاً لتأثير نوع المواد على الاجهادات الناتجة عبر دراسة تأثير تغير مواد عناصر الوصلة (العصب و الصفيحة) على قيم الاجهاد الناتج حتى درجة الانهيار.  اختيرت العناصر من عدة مواد و خلائط مكونة من عناصر كيميائية مختلفة حيث تم حساب الإجهادات الناشئة بعد تصميم ونمذجة كل وصلة لكل خالة مع مادة عصب وصفيحة مختلفة بوجود درجات الحرارة اعتبارا من درجة حرارة الوسط المحيط حتى درجة انصهار الخلائط المدروسة .في هذه المقالة المتغير الوحيد كان نوع المادة والعناصر الكيميائية في حين تم تثبيت كافة البارامترات الأخرى للوصلة (الابعاد_الشكل_نوع الوصلة_شروط التثبيت و...) وذلك ليكون فهم تأثير نوع الصفيحة والعصب أوضح على قيم الإجهادات الناشئة في الوصلة حيث توجد عوامل عديدة أخرى قد تؤثر على قيم الاجهادات كوجود أكثر من نوع للحمولة وحدوث تشققات داخلية في المعدن ناتجة عن عمليات التشغيل إلخ....